Identifikasi Pengenalan Makanan Tradisional dalam Pembelajaran sebagai Muatan Lokal di PAUD Sekecamatan Cakranegara Kota Mataram - Wulandhari, Ni Luh Vidya; Astini, Baik Nilawati; Rachmayani, Ika (Indonesian Publication Center, 2024)
This study aims to determine the traditional foods that have been introduced, the dominant traditional foods introduced and the dominant traditional foods requested by children to be remade and to know the steps of introducing traditional foods. The population in this study amounted to 124 teachers with a sample of 12 PAUD teachers in Cakranegara District, Mataram City. This research is a survey research and uses data collection methods in the form of questionnaires and observation and data analysis techniques using the percentage formula. The results of this study indicate that traditional foods that have been introduced include plecing, satay bulayak, beberuk, cerorot, jaje opak, taliwang grilled chicken, klepon, spring rolls, getuk lindri, onde-onde and nagasari while the dominant ones introduced are plecing and klepon (66%) and the dominant ones asked by children to be remade are klepon (50%). The media used in the introduction is in the form of food or direct objects, visual and audio visual and the methods used are demonstration methods, direct practice and question and answer. The introduction of materials and tools is introduced by mentioning and explaining with the objects directly and the way of making is introduced by mentioning, explaining and direct practice as well as the provision of the necessary materials and tools provided by the school and most of the traditional foods are introduced several times during 1 year and most of them are introduced on Saturday week 3.